IDENTIFYING CHALLENGES AND PROPOSING SOLUTIONS IN TEACHING ENGLISH AT MILITARY-ORIENTED LYCEUMS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The process of teaching English in military-oriented lyceums involves specific difficulties and problems. These problems can be related to students ' motivation in language learning, methodological approaches, teacher qualifications, correspondence of textbooks and teaching materials, as well as requirements specific to the military direction. This article analyzes the main problems that arise when teaching English in military lyceums and offers effective solutions to solve them.